مجاز قرآنیہ: قائلین مجاز کے استدلات کا تجزیہ: QUR'ANIC METAPHOR: AN ANALYSIS OF THE ARGUMENTS OF ITS PROPONENTS (Al-Aasar, 2025)
This article explores the concept of majaaz (figurative language or metaphor) within the Qur'an and its importance in the divine text. The research discusses the historical evolution and acceptance of majaaz across various Islamic fields, including linguistics, grammar, tafsir, hadith, and Islamic jurisprudence. Famous scholars from the second to the ninth Hijri century are analyzed to underscore their perspectives and arguments regarding majaaz. Through examination of their writings, the article illustrates how majaaz functions in interpretations. This study reaffirms that majaaz is not only acceptable but also essential in describing the profound depth and miraculous eloquence of the Qur'anic message.